'From soil to chocolate bar': identifying critical steps in the journey of cadmium in a Colombian cacao plantation. Issue 5 (4th May 2022) - Bravo, Daniel; Santander, Margareth; Rodríguez, Jader; Escobar, Sebastian; Ramtahal, Gideon; Atkinson, Rachel
Abstract: Regulation of maximum levels of cadmium in chocolate is an issue for cacao exportation from many parts of Latin America, including Colombia. These limits are related to the final product, but buyers often request maximum levels of Cd in the beans. However, to date, there is neither a clear understanding of the relationship between the specified levels of Cd in chocolate and cocoa derivatives and levels in harvested beans or soil nor of the effect of post-harvest processes on the levels of Cd in the final product. To address this, the fate of Cd concentration from soil to chocolate bar was followed in a single farm in Santander district, Colombia. The concentration of Cd in soils was measured using ICP-OES and correlated with soil pH, soil organic matter (SOM), and the use of P-based fertilisers. Cd concentrations were also measured in unfermented seeds, fermented and dried beans, shell, nibs, and chocolate. SOM (2.93–3.78%), soil pH (4.7–4.9), soil P concentration (120–132 mg kg −1 ) affect Cd availability. However, it is still unclear whether Cd concentration of P-based fertilisers (3–30 mg kg −1 ) is important or not. While post-harvest treatments did not affect the Cd concentration of beans (4.17 ± 0.8 mg kg −1 on average), the removal of the shell (6.57 mg kg −1 ) from the nibs (3.28 mg kg −1 ), as well as the percentage of cocoa mass used contributes to a reduction in Cd concentration in the chocolate bar (1.60 mg kg −1 ). This study provides clear indications on where research into mitigation measures should be focussed, as well as indicating the importance of carrying out analyses for Cd in the nib or cacao mass, rather than the whole bean, reducing Cd concentration by up to 40%. Graphical Abstract: UF0001